PEMBERDAYAAN MASYARAKAT DESA DUSUN ANYAR DALAM GERAKAN PEDULI LINGKUNGAN DAN SADAR STUNTING - Dewi Handayani; Muhammad Robi; Rina Elvia; Hermansyah Amir (Universitas Bengkulu, 2023)
The aim of this activity is to help provide understanding to the community and provide information and education about the importance of preserving environmental functions and preventing environmental damage as well as education about the importance of preventing stunting to all levels of community in Dusun Anyar Village in order to realize the Indonesian government's national goals in the stunting reduction program. in Indonesia. The activity method carried out is through outreach activities about environmental conservation and education about stunting. The activity was attended by 50 participants consisting of children, teenagers and adults. With the activities planned, it can help provide understanding to the community and provide information and education about the importance of preserving environmental functions and preventing environmental damage and preventing stunting. Keywords: Service, Environment, Stunting